Implementation of Continuing Professional Development Seminar: Input to CPD Provider Enhancement (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2021)
In today’s modern era, the educational system demands continuing research, training, and seminar to meet professional needs. It showed a direct influence on the continuing advancements in modern clinical pedagogy. Continuing Professional Development (CPD) in nursing aims to improve and assimilate the praxis learned from theoretical knowledge into real-life clinical situations. Nurses need to undergo intensive training to function efficiently in delivering holistic care. On the contrary, developing effective methods to prepare and enhance their skills and clinical performance remains pedagogical. Hence, this study determined the implementation of CPD seminars as an input to CPD provider enhancement. The research utilized the quantitative descriptive research design. A purposive sampling method was utilized, and there was a complete enumeration of respondents who met the inclusion and exclusion criteria. A self-made evaluative tool was used to gather data regarding the implementation of the CPD seminar and tested for its validity and reliability. The responses of the respondents on the discussion of the importance of OBE and entrepreneurship in the nursing profession were excellent, along with content (80%), relevance (80%), and application (64%). Answers on the discussion of the importance of rubrics and table of the specification were also excellent, along with content (80%), relevance (87%), and application (64%). Moreover, results on the importance of OBE and entrepreneurship in the nursing profession along with content (84%), relevance (89%), and application (78%). For the venue or the physical set-up, the sound system and ventilation were rated as excellent (78%), followed by the registration procedure and participation of the delegates who evaluated it as satisfactory (62%). Participants value the contents of the seminar for it can help them in their future endeavors, and the topic covered was relevant and useful to broaden their knowledge and skills development throughout their career. Data revealed that the seminar is significant, and it created an impact on the participant's careers, for they can put the theory learned into praxis. Considering the preceding conclusions, the researchers have cited recommendations to include inferential statistics in its data analysis—a relatively increased number of participants who can have the chance to participate in the study. And to further warrants stakeholders, health authorities, and health workers to devise flexible CPD seminars for nurses to ensure sustainability and efficacy of such CPD program providers.
Keywords: Continuing Professional Development, Outcomes-Based Education, Rubrics, Table of Specification, Nursing Entrepreneurship